RADIO FREQUENCY SPECTRUM MANAGEMENT IN THE KYRGYZ REPUBLIC: CHALLENGES, SOLUTIONS, AND AUTOMATION PROSPECTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The radio frequency spectrum (RFS) is one of the most important resources for the functioning of telecommunications systems, broadcasting, television, and national security. This article discusses the main principles of radio frequency spectrum management, including its natural and technical features, methods of frequency planning and allocation. Special attention is given to the role of process automation in spectrum management using modern software products and geographic information systems (GIS). The article also explores key challenges faced by Kyrgyzstan in spectrum management, including the lack of qualified specialists, limited funding, and the need for international coordination. Recommendations are provided for improving legislation, implementing new technologies, strengthening international cooperation, and developing the radio frequency monitoring infrastructure in Kyrgyzstan. The automation of RFS management, the use of artificial intelligence (AI), and GIS open new prospects for enhancing the efficiency of the limited radio frequency resource use.
Keywords: Radio frequency spectrum, spectrum management, automation, geographic information systems, radiocommunication, electromagnetic compatibility, licensing, radiomonitoring, artificial intelligence, 5G, Internet of Things (IoT), international cooperation, Kyrgyzstan.